Síndrome Inflamatória Multissistémica Pediátrica Temporalmente associada à COVID-19: uma revisão sistemática - Daniela Neves Guimarães (2021)
Despite milder COVID-19 presentations in children, a recent condition termed Pediatric Inflammatory Multisystem Syndrome Temporally associated with SARS-CoV-2 (PIMS-TS) has been recognized. An extensive literature search was conducted in MEDLINE, Scopus and Web of Science, considering only PIMS-TS case definitions. 31 included studies, reporting 1415 patients. Most studies reported a median age of nine years-old, male prevalence (1∙6:1) and a majority of African/Hispanic descent. Obesity was the most stated comorbidity. Common symptoms included: gastrointestinal (70%), rash (57%) and cardiovascular (52% with shock). Notable differences with Kawasaki Disease were identified. 30% presented positive SARS-CoV-2 RT-PCR and 51% positive serologies. 62% received intravenous immunoglobulin and 42% glucocorticoids. 62% required intensive care, 21 children died (<2%). Severe presentations were associated with higher levels of certain inflammatory/cardiac biomarkers, IgG titers, neurological symptoms, hepatitis and acute kidney injury. This review provides global insights into current practice. Further studies are needed to determine optimal clinical management.